Comparative Analysis Of The Use Of Modern And Traditional Methods Of Education In Higher Education - Rustamov Mirodiljon Muhammadjonovich (Periodica Journal, 2023)
This article presents the results of research on the use of effective methods and means of teaching students in higher educational institutions. The relevance of the article lies in the fact that it examines the practical significance of using new teaching methods in the training of highly qualified personnel in accordance with the requirements of the time, as well as the possibility of choosing teaching methods used to determine the level of their effectiveness. Two teaching methods used to determine the effectiveness of teaching the subject of information technology in higher education were studied, namely the effectiveness of traditional educational technologies and interactive educational technologies. A comparative analysis of the use of modern technologies of experimental and control groups was carried out.
Keywords: determine; groups; level